Performance Analysis of a Multisensor IoT System for Water Quality Surveillance at PDAM Makassar - Muhammad Syafaat; Jeffry Jeffry (Journal of Innovative and Creativity, 2025)
IoT-Based Water Monitoring System with Case Study of Makassar City PDAM is a tool made to provide convenience to PDAM (Regional Drinking Water Company) employees, especially at Makassar City PDAM, to determine the pH value of water, TDS value and NTU level value in water reservoirs using a water pH sensor, TDS sensor and LDR sensor which will be displayed on a website application via an internet network in the form of a graph. If the pH value read on the water pH sensor is pH 6.5-8.5, it can be declared that the water is in proper condition, if the ppm value read to the TDS sensor is 0-300 ppm, the water is declared proper and if the ppm value read to the LDR sensor is 0-25 NTU, the water is declared proper. the parameter accuracy rate of the pH Sensor is 94.74%, the TDS Sensor is 93.70%, while the Water Turbidity sensor has an accuracy rate of 85.31% so that the overall accuracy rate of this consumable water monitoring system is 91.25%.